PHRASEOLOGY OF “THE ABSOLUTE MISTER OF FORM” - Лесюк, М. П.; Попойлик, Ю. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article of Mykola Lesiuk and Yulia Popoylyk Phraseology of “the absolute mister of form” one analyses the phraseological units, which richly scatter texts of novellas written by Vasyl Stefanyk. The author uses along with them and nationwide phrasemics, but the majority of the fixed word combinations belong to the creations of the author himself, an outstanding master of artistic word. In the article the various groups of phraseological units are analyzed; their particular classification is conducted.